Modelación del proceso de gasificación de biomasa en un reactor de lecho fijo con calentamiento indirecto (2018)
The present project arises from the interest of the research group of Alternative Energies for knowing and evaluating the utility of the process of gasification of residual biomass to obtain a synthesis gas, which after subsequent physical and chemical transformations, can be used as gas. The energetic and efficient use of this sustainable energy source, drives the development of a theoretical-mathematical model and the solution of it with the aim of obtaining a better visualization of the distribution of resulting products after the completion of the process. As an added value for the model that will be carried out, the fixed-bed reactor has indirect heating.